Specification and estimation of rating scale models: With an application to the determinants of life satisfaction - Raphael Studer; Rainer Winkelmann (University of Zurich, Department of Economics, 2011)
This article proposes a new class of rating scale models, which merges advantages and overcomes shortcomings of the traditional linear and ordered latent regression models. Both parametric and semi-parametric estimation is considered. The insights of an empirical application to satisfaction data are threefold. First, the methods are easily implementable in standard statistical software. Second, the non-linear model allows for exible marginal effects, and predicted means respect the boundaries of the dependent variable. Third, average marginal effects are similar to ordinary least squares estimates.
Keywords: C21; I00; 330; rating variables; non-linear least squares; quasi-maximum likelihood; semiparametric least squares; subjective well-being; Regression; Nichtparametrisches Verfahren; Maximum-Likelihood-Methode; Methode der kleinsten Quadrate; Theorie